2021
DOI: 10.3390/toxins13060374
|View full text |Cite
|
Sign up to set email alerts
|

Early Botulinum Toxin Type A Injection for Post-Stroke Spasticity: A Longitudinal Cohort Study

Abstract: Early management of spasticity may improve stroke outcome. Botulinum toxin type A (BoNT-A) is recommended treatment for post-stroke spasticity (PSS). However, it is usually administered in the chronic phase of stroke. Our aim was to determine whether the length of time between stroke onset and initial BoNT-A injection has an effect on outcomes after PSS treatment. This multicenter, longitudinal, cohort study included stroke patients (time since onset <12 months) with PSS who received BoNT-A for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…It has been reported in previous literature that delivery of injections without instrumental guidance was practiced in 25% of post-stroke spasticity cases [25]. Most importantly, late management of a significant number of post-stroke spasticity cases has been reported, which increases the likelihood of severe muscle hypertonia and contracture, emphasizing the importance of early planning of treatment for stroke survivors [26]. On the other hand, BTX injections have shown long-term prophylaxis of chronic migraine with good tolerability and improvement of quality of life in severe persistent cases by decreasing the incidence of depression and enhancing work productivity [27][28].…”
Section: Demand For Structured Training Programs Regarding the Non-co...mentioning
confidence: 99%
“…It has been reported in previous literature that delivery of injections without instrumental guidance was practiced in 25% of post-stroke spasticity cases [25]. Most importantly, late management of a significant number of post-stroke spasticity cases has been reported, which increases the likelihood of severe muscle hypertonia and contracture, emphasizing the importance of early planning of treatment for stroke survivors [26]. On the other hand, BTX injections have shown long-term prophylaxis of chronic migraine with good tolerability and improvement of quality of life in severe persistent cases by decreasing the incidence of depression and enhancing work productivity [27][28].…”
Section: Demand For Structured Training Programs Regarding the Non-co...mentioning
confidence: 99%
“…To avoid this potentially damaging effect, a tempestive treatment, integrated with early stretching treatment, could be a proper strategy. Indeed, even if BoNT-A injections are the gold standard in patients with spasticity in the chronic phase of stroke ( 44 ), recent studies showed that BoNT-A treatment performed within 3 months since stroke onset in naïve patients with spasticity can achieve the maximum effect on muscle tone, allowing better control of spasticity in chronic phase and a reduction of serial injections ( 45 47 ). Moreover, a careful systematic follow-up of treated patients is necessary ( 48 ).…”
Section: Morphological Changesmentioning
confidence: 99%
“…Italy, as well as other nations, does not have a consistent clinical care model for the treatment of post-stroke spasticity with BoNT-A and the routine use of botulinum toxin in clinics is far from standardized [ 17 ]. Notwithstanding a massive literature supporting the efficacy of BoNT-A for the treatment of PSS, there still are shortcomings in the routine management of PSS patients [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%